Fetal Links to Chronic Disease: The Role of Gestational Diabetes Mellitus - Durnwald, Celeste; Landon, Mark (American Journal of Perinatology, 2013)
A growing body of literature suggests that chronic disease has much of its origins in the fetal response to the intrauterine environment, a concept known as “fetal programming.” Longitudinal studies have demonstrated that higher rates of obesity, impaired glucose tolerance, hypertension, and dyslipidemia are evident in the offspring of diabetic women. This review focuses on the implications of intrauterine exposure to an altered maternal metabolic milieu and the risk of childhood obesity and metabolic dysfunction.
Keywords: gestational diabetes; fetal programming; childhood obesity; impaired glucose tolerance in offspring